ABINITIO SIMULATION OF ELECTRON-TRANSFER REACTIONS - THE REACTION OF ALKALI-METAL ATOMS WITH ETHYLENE - Hänsele, Elke; Clark, Timothy (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 1991)
The one-electron reduction of ethylene by alkali-metal atoms (Li, Na, K, Rb) has been investigated using ab initio molecular orbital theory. The gas-phase behavior of the metals is dominated by the electrostatic ion-pair energy in the M+:C2H4.- products. Lithium the smallest of the alkali metals, therefore gives the least endothermic reaction energy (M. + C2H4 –> M+:C2H4.-) in the gas phase. Self-consistent reaction field (SCRF) theory has been used to investigate the effect of solvent on the electron transfer reactions. The solvent effect is small for M = Li, but larger for the heavier metals, so that rubidium becomes comparable to lithium in polar solvents. The activation energy for the electron transfer reaction itself has been estimated for lithium using a linear synchronous transit between the reactant and product geometries.
Keywords: ELECTRON TRANSFER; ABINITIO MO THEORY; SCRF THEORY; ALKALI METAL REDUCTION